Gratian’s Concordia discordantium canonum in the context of the conflict between imperium and sacerdotium in the medieval Europe - Ryguła, Piotr (The Opole Studies in Administration and Law, 2017)
Primarily, Gratian is known as the author of the Concordia discordantium canonum and is regarded as the “Father of Canon Law” and the most famous canonist. In the title of the Decretum he included an idea which accompanied him during his work: it was reconciliation and coordination of inconsistent canons. As a lecturer of the School of the Law in Bologne he knew how important cohesion in law was and as a follower of the Gregorian Reform he knew, too, how important the Canon Law was in the dispute between imperium and sacerdotium. Both factions, i.e., the Holy Roman Emperor and the Pope, in their right argumentation, appealed to the recognized authorities and the law. Both needed the law itself internally consistent as a source of these arguments. These issues, as mentioned in the title, are discussed by the author of the present article.